Evaluación del uso de los Residuos de cascarilla de arroz (Oryza sativa L.) como agregado en bloques para la construcción. - Demera Centeno, Santiago David (2018)
The objective of the present investigation was to evaluate the use of rice husk waste as an aggregate for the construction of blocks in the construction. Initially, a survey was applied to seven mills in Rocafuerte canton to know the amount of rice husk generated in a week. To obtain the blocks, three treatments were established and a control based on the dosage of rice husk T1 (25% - 0.31 kg); T2 (50% - 0.61 kg); T3 (75% - 0.91 kg) and control (100% - 0 kg). The blocks were subjected to resistance tests and those results analyzed through the InfosTat software. According to the survey carried out, the collection centers that generate the largest amount of rice husks are San Vicente and Santa Mónica with 200 quintals / week each, Las Jaguas with a production of 175 quintals / week, while the pellet mill generates less rice husk is San Juan with 100 quintals per week. A total of 48 blocks were included, including ecological and traditional or witnesses. According to the compression tests, the block at 28 days with a 25% rice husk dosage showed the highest resistance (36 kg / cm2), a value that approaches the traditional block, which allowed concluding that the ecobloc meets with the parameters of mechanical strength in force in the INEN 3066 (2016), according to the statistical analysis there are significant differences between each of the treatments.